Devil bones : [compact disc, unabridged] : a novel - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series., 2008)
In a house under renovation, a plumber uncovers a cellar no one knew about, and makes a rather grisly discovery -- a decapitated chicken, animal bones, and cauldrons containing beads, feathers, and other relics of religious ceremonies. In the center of the shrine, there is the skull of a teenage girl. Meanwhile, on a nearby lakeshore, the headless body of a teenage boy is found by a man walking his dog. Nothing is clear -- neither when the deaths occurred, nor where. Was the skull brought to the cellar or was the girl murdered there? Why is the boy's body remarkably well preserved? Led by a preacher turned politician, citizen vigilantes blame devil worshippers and Wiccans. They begin a witch hunt, intent on seeking revenge. Forensic anthropologist Temperance Brennan -- "five-five, feisty, and forty-plus" -- is called in to investigate, and a complex and gripping tale unfolds in this, Kathy Reichs's eleventh taut, always surprising, scientifically fascinating mystery.